1990
DOI: 10.1095/biolreprod43.5.812
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cytokines on Porcine Granulosa Cell Steroidogenesis in Vitro1

Abstract: Recent evidence indicates that factors produced by immune cells (cytokines) may play a role in ovarian function. To explore this possibility, we examined the effects of conditioned medium obtained from cultures of either unstimulated splenocytes (splenocyte-conditioned medium; SCM) or concanavalin A-stimulated splenocytes (CAS) on estrogen and progesterone production by porcine granulosa cells. Granulosa cells were obtained from small (less than 3 mm) or large (greater than 7 mm) follicles and treated with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Our studies also indicate that the granulosa cell responsiveness to cytokines is dependent on size of follicle. Similarly, previous studies have indicated that the response of granulosa cells from small porcine follicles to conditioned medium from cultured splenocytes (a source of cytokines) is different from that of granulosa cells from large porcine follicles [16]. Why granulosa cells from large bovine follicles are 40 times less sensitive to IL-6 than granulosa cells from small bovine follicles is uncertain.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our studies also indicate that the granulosa cell responsiveness to cytokines is dependent on size of follicle. Similarly, previous studies have indicated that the response of granulosa cells from small porcine follicles to conditioned medium from cultured splenocytes (a source of cytokines) is different from that of granulosa cells from large porcine follicles [16]. Why granulosa cells from large bovine follicles are 40 times less sensitive to IL-6 than granulosa cells from small bovine follicles is uncertain.…”
Section: Discussionmentioning
confidence: 98%
“…Other potential sources of cytokines within the ovary include the CL [12,13] and various immune cells [14,15]. Whether cytokines differentially affect granulosa cell functions in small and large follicles is unknown, although a recent study indicates that granulosa cells from small and large follicles respond differently to conditioned medium from cultured splenocytes (a source of cytokines) [16]. Also, reports on direct effects of cytokines on aromatase activity of bovine ovarian cells are meager.…”
Section: Introductionmentioning
confidence: 99%
“…Functions of immuno-peptides outside of the regulatory and control aspects on the immune system are now being elucidated (Adashi, 1990;Pollanen et al, 1990). Secretory products from media of macrophage, splenic, and thymic cell cultures can stimulate (Yee and Hutson, 1985;Gorospe and Kasson, 1988;Hughes et al, 1990;Uzumcu and Lin, 1994) or inhibit ovarian and testicular steroidogenesis (Aguilera and Romano, 1989;Reyes-Esparza and Romano, 1989;Watson et al, 1994). Within the testis reside numerous immune cells (Hermo and Lalli, 1978;Pollanen and Maddocks, 1988;Setchell et al, 1990;Bergh et al, 1993;Gaytan et al, 1994;Pinilla et al, 1994;Wang et al, 1994), and the potential for local immunoregulation of testicular function is under evaluation Skinner, 1991;Hutson, 1992;Gaytan et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The luteotrophic and luteolytic nature of immune factors depends on the luteal environment, particularly on the absence of immunosuppressive factors such as progesterone (Walusimbi and Pate 2013). Macrophages likely play a crucial role in the resolution of the luteolytic process and avoidance of an inflammatory response (Pate and Keyes 2001), whereas T lymphocytes enhance progesterone production in the CL of several species(Emi et al 1991, Hughes et al 1990. On the other hand, progesterone inhibits lymphocyte proliferation and interferes with the cytokine action on the luteal cells (reviewed bySiiteri and Stities 1982, Grossmanm 1984, Kelly 1994).…”
mentioning
confidence: 99%